The Negative Impact of Using Application TikTok Regarding Intelligence Level Children's Emotions Towards Islamic Religious Education - Hasibuan, Hamdan; lubis, Eva Monika Safitri (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2024)
Current technological developments are growing rapidly, a lot children who use cellphones for watch videos. One of the current media this is a lot interested that is tiktok. TikTok’s video can influence intelligence emotional of children, so happen a problem about How impact negative from tiktok videos on intelligence emotional child aged 13-15 years and Islamic religious education . Methodology study This use approach qualitative that is research conducted with method observe existing phenomena around it and analyze it with use logic scientific. Research results in Lumban DolokVillage show that there are impact negative of tiktok videos on intelligence emotional children,between teenager beginning aged 13-15 years in this village Lots experience changes in yourself them each after know application tiktok , Excessive emotional , brave denied parents , wasted time waste of time Study drained For things that don't important , difficult get along with environment around , excessive selfishness , no care the surroundings , it 's easy angry and aggressive